Evaluation of personal inhalable aerosol samplers with different filters for use during anthrax responses. Issue 8 (3rd August 2017) - Grinshpun, Sergey A.; Weber, Angela M.; Yermakov, Michael; Indugula, Reshmi; Elmashae, Yousef; Reponen, Tiina; Rose, Laura
ABSTRACT: Risk of inhalation exposure to viable Bacillus anthracis ( B. anthracis ) spores has primarily been assessed using short-term, stationary sampling methods which may not accurately characterize the concentration of inhalable-sized spores reaching a person's breathing zone. While a variety of aerosol sampling methods have been utilized during previous anthrax responses, no consensus has yet been established for personal air sampling. The goal of this study was to determine the best sampler-filter combination(s) for the collection and extraction of B. anthracis spores. The study was designed to (1) evaluate the performance of four filter types (one mixed cellulose ester, MCE (pore size = 3 µm), two polytetrafluoroethylene, PTFE (1 and 3 µm), and one polycarbonate, PC (3 µm)); and (2) evaluate the best performing filters in two commercially available inhalable aerosol samplers (IOM and Button). Bacillus thuringiensis kurstaki [Bt(k)], a simulant for B. anthracis, served as the aerosol challenge. The filters were assessed based on criteria such as ability to maintain low pressure drop over an extended sampling period, filter integrity under various environmental conditions, spore collection and extraction efficiencies, ease of loading and unloading the filters into the samplers, cost, and availability. Three of the four tested collection filters—except MCE—were found suitable for efficient collection and recovery of Bt(k) spores sampled from dry and humid as well as dusty and clean air environments for up to 8 hr. The PC (3 µm) filter was identified as the best performing filter in this study. The PTFE (3 µm) demonstrated a comparable performance, but it is more expensive. Slightly higher concentrations were measured with the IOM inhalable sampler which is the preferred sampler's performance criterion when detecting a highly pathogenic agent with no established "safe" inhalation exposure level. Additional studies are needed to address the effects of environmental conditions and spore concentration. The data obtained in this investigation are crucial for future efforts on the development and optimization of a method for assessing inhalation exposure to B. anthracis .